CDR 2021
DOI: 10.20517/cdr.2021.07
|View full text |Cite
|
Sign up to set email alerts
|

Emerging RAS-directed therapies for cancer

Abstract: RAS oncogenes are the most commonly mutated oncogenes in human cancer, and RAS-mutant cancers represent a major burden of human disease. Though these oncogenes were discovered decades ago, recent years have seen major advances in understanding of their structure and function, including the therapeutic and prognostic significance of diverse isoforms. Targeting of these mutations has proven difficult, despite some successes with inhibition of RAS effector signalling. More recently, direct RAS inhibition has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…52 Despite the enormous studies conducted, RAS, however, stood apart; it is allegedly termed "undruggable" and direct RAS inhibitor development proved exceedingly challenging. 53 Direct drugging of RAS protein was considered paradoxical due to the absence of a drug-binding pocket; consequently, studies started focusing on the proteins upstream and downstream of RAS that could help suppress the oncogenic signal. 41 Albeit drugging RAS had initial failures, tremendous efforts in understanding the complications of RAS have initiated new avenues for next-generation anti-RAS drug discovery by NCI (National Cancer Institute).…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…52 Despite the enormous studies conducted, RAS, however, stood apart; it is allegedly termed "undruggable" and direct RAS inhibitor development proved exceedingly challenging. 53 Direct drugging of RAS protein was considered paradoxical due to the absence of a drug-binding pocket; consequently, studies started focusing on the proteins upstream and downstream of RAS that could help suppress the oncogenic signal. 41 Albeit drugging RAS had initial failures, tremendous efforts in understanding the complications of RAS have initiated new avenues for next-generation anti-RAS drug discovery by NCI (National Cancer Institute).…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…To further determine the method's feasibility, these chemical modifications on wider ranges of proteins via the lysine-based ligation have been conveyed (SI Figures S3−16). Specifically, lysozyme, myoglobin, RNase A, HRAS, KRAS, 29 as well as MiaA (tRNA dimethylallyl transferase) 30 were intensively evaluated. The Western blotting assays indicated that the treatment with chemical reagents (1-NO pyrene, 2t, 50 μM or 100 μM) led to a minimal effect on those proteins when staining with GoldView, although the in-gel blue fluorescence varied for each of those proteins.…”
Section: Explorations Of the Reaction On Proteinsmentioning
confidence: 99%
“…Based on this mechanism, bisphosphonates are mainly prescribed in patients with Paget disease of the bone, osteoporosis, myelomas and bone metastases [ 94 ]. Farnesyltransferase inhibitors (e.g., lonafarnib, tipifarnib) were developed as anti-cancer agents to specifically disrupt Ras farnesylation [ 96 ]. Geranylgeranyl transferase inhibitors (e.g., GGTI-2148, GGTI-298, P61A6) were developed to target downstream oncogenesis of Ras and are potent in inducing apoptosis as well as G1 phase cell-cycle arrest [ 97 ].…”
Section: Targeting the Mevalonate Pathwaymentioning
confidence: 99%